Open-ended urethral catheters reduce catheter obstruction after hypospadias repair - Zhao, Xiang; Yu, Kechi; Fang, Erhu; Li, Ning (Frontiers in Pediatrics, 2024)
BackgroundsUrethral catheter obstruction is a notable issue that pediatric patients with hypospadias may encounter in the early postoperative period. This retrospective study aims to assess the efficacy of open-ended urethral catheters with 2 side holes in mitigating catheter obstruction in pediatric patients following hypospadias repair.Materials and methodsThe clinical data of pediatric patients who underwent hypospadias repair surgery from January 2021 to October 2023 were retrospectively collected. The patients were divided into 2 groups. Those who used standard Foley catheters were referred to as Group A, while those who used modified open-ended catheters were referred to as Group B. The primary outcome was the incidence of catheter obstruction within 7 days postoperatively.ResultsA total of 297 patients were included in this study, with 142 patients in Group A and 155 patients in Group B. In Group A, there were 12 cases of catheter obstruction, with 10 cases resolved through irrigation and 2 cases requiring additional catheters insertion by suprapubic bladder punctures. In Group B, only 4 cases experienced catheter obstruction, which were effectively and easily resolved through maneuver irrigation. The incidence of catheter obstruction in Group B was statistically significantly lower than that in Group A (2.6% vs. 8.5%, p < 0.05).ConclusionIn pediatric hypospadias patients who underwent surgical repair, the use of open-ended urethral catheters with 2 side holes significantly diminishes the incidence of postoperative catheter obstruction. This simple technique is worthy of promotion.